2020
DOI: 10.32448/entupdates.718393
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of orbital floor fractures using a porous polyethylene implant: outcomes in the early, intermediate and late postoperative periods

Abstract: Objective: The porous polyethylene implant (PPEI) is one of the most commonly used alloplastic materials in cranio-maxillofacial surgery. It is widely preferred because of its biocompatible, durable, flexible and thin nature as well as for its low complication rates. The purpose of the present study was to review the clinical and surgical outcomes of PPEI usage for orbital floor fractures. Methods: The present study included 76 patients who underwent orbital floor fracture reconstruction using PPEI between Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…While it lacks radiodensity and might not be easily visualized on post-operative CT scans, Medpor is generally well-received by the body and its porous architecture enables the formation of fibrovascular networks, serving as a safeguard against infections and implant displacement [66]. Other research has confirmed that its clinical outcomes are generally favorable, although some cases of immediate and long-term complications, such as surgical site infection, cyst formation, delayed atraumatic hematoma, and implant extrusion, have been reported [26,[67][68][69][70].…”
Section: Porous Polyethylene (Pe)mentioning
confidence: 99%
“…While it lacks radiodensity and might not be easily visualized on post-operative CT scans, Medpor is generally well-received by the body and its porous architecture enables the formation of fibrovascular networks, serving as a safeguard against infections and implant displacement [66]. Other research has confirmed that its clinical outcomes are generally favorable, although some cases of immediate and long-term complications, such as surgical site infection, cyst formation, delayed atraumatic hematoma, and implant extrusion, have been reported [26,[67][68][69][70].…”
Section: Porous Polyethylene (Pe)mentioning
confidence: 99%
“…However, for all other evaluated parameters, both groups showed comparable outcomes [ 33 ]. Despite its general acceptance, complications such as implant extrusion and infection have been reported [ 34 , 35 , 36 ].…”
Section: Oculoplastic and Orbital Surgery Devicesmentioning
confidence: 99%